1989
DOI: 10.1007/bf01958280
|View full text |Cite
|
Sign up to set email alerts
|

4-Hydroxybutyric aciduria: Further clinical heterogeneity in a new case

Abstract: A 2.5-year-old girl presented with severely delayed speech development and mild motor retardation. Urinary organic acid analysis showed the presence of 4-hydroxybutyric acid and other metabolites consistent with the diagnosis 4-hydroxybutyric aciduria. Succinic semialdehyde dehydrogenase activity was absent in lymphocyte lysates. The clinical symptoms in this case were unusually mild compared to previously reported patients. No correlation was found between the mild symptoms and the levels of metabolite excret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Case ascertainment dating back to the initial report of gamma-hydroxybutyric aciduria identified 91 unique patients with clinical details provided (Aoshima et al 2002;Bekri et al 2004;Brown et al 1987;Dayan et al 2006;Deng et al 2011;Divry et al 1983;Escalera et al 2010;Gogou et al 2016;Haan et al 1985; Ishiguro et al 2001; Jakobs et al 1981;Jiang et al 2013;Kratz 2009;Kwok et al 2012;Lemes et al 2006;Li et al 2015;Lin et al 2015;Liu et al 2016;Neu et al 2002;Niemi et al 2014;O'Rourke et al 2010;Onkenhout et al 1989;Pearl et al 2003;Peters et al 1999;Puttmann et al 2013;Racaru et al 2010;Rashed et al 1994;Rating et al 1984;Saronwala et al 2008;Spilioti et al 2013;Tay et al 2015;Wang et al 2016;Yamakawa et al 2012;Zhao et al 2003;Ziyeh et al 2002). We furthermore identified 91 additional subjects with confirmed SSADH deficiency in our database published in aggregate (Parviz et al 2014).…”
Section: Case Reports and Resultsmentioning
confidence: 99%
“…Case ascertainment dating back to the initial report of gamma-hydroxybutyric aciduria identified 91 unique patients with clinical details provided (Aoshima et al 2002;Bekri et al 2004;Brown et al 1987;Dayan et al 2006;Deng et al 2011;Divry et al 1983;Escalera et al 2010;Gogou et al 2016;Haan et al 1985; Ishiguro et al 2001; Jakobs et al 1981;Jiang et al 2013;Kratz 2009;Kwok et al 2012;Lemes et al 2006;Li et al 2015;Lin et al 2015;Liu et al 2016;Neu et al 2002;Niemi et al 2014;O'Rourke et al 2010;Onkenhout et al 1989;Pearl et al 2003;Peters et al 1999;Puttmann et al 2013;Racaru et al 2010;Rashed et al 1994;Rating et al 1984;Saronwala et al 2008;Spilioti et al 2013;Tay et al 2015;Wang et al 2016;Yamakawa et al 2012;Zhao et al 2003;Ziyeh et al 2002). We furthermore identified 91 additional subjects with confirmed SSADH deficiency in our database published in aggregate (Parviz et al 2014).…”
Section: Case Reports and Resultsmentioning
confidence: 99%
“…We also report a range of EEG findings based on a literature review capturing 25 published cases with EEG data available [11][12][13][14][15][16]18,19 and combined with 9 patients from our cohort (see table 2). Abnormalities include generalized and focal epileptiform discharges, photosensitivity, background slowing, and sleep spindle asynchrony.…”
Section: Resultsmentioning
confidence: 99%
“…Abnormalities include generalized and focal epileptiform discharges, photosensitivity, background slowing, and sleep spindle asynchrony. [11][12][13][14][15][16][17][18][19]21 These revealed T2 hyperintensities in multiple regions, most commonly of the globus pallidus (see table 2). The explanation for epilepsy in nearly half of SSADH-deficient patients is unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Electroencephalographic studies have disclosed a variety of background abnormalities and epileptiform features. On the basis of a review of 35 cases having electroencephalographic data available, we reported spike discharges (focal and generalized) in 8 of 34 patients (24%), photoparoxysmal response in 1 patient, background slowing in 8 patients, sleep spindle asynchrony in 1 adult patient, and lack of stage rapid eye movement on one overnight study 4, 10, 12–15, 22, 23, 25. There were normal recordings in 16 patients (46%).…”
Section: Neurophysiologymentioning
confidence: 99%